Environmental Impact Analysis of Leather Production Using The Life Cycle Assessment and Analytical Network Process Methods - Rahmadsyah, Mohamad Faris; Pulansari, Farida; Dewi, Sinta (CV. Literasi Indonesia, 2025)
The leather industry is one of the fields that produces hazardous waste for the environment. One example is CV XYZ, a leather manufacturing company based in East Java, Indonesia. Liquid waste produced per production batch is over 4,000 liters and the electricity consumed is a maximum of 5,000 kWh per month. This study focuses on the environmental impacts in the leather production process of the CV XYZ using the Life Cycle Assessment (LCA) method. Additionally, the Analytical Network Process (ANP) method is used to select alternative improvements given that it minimizes environmental impact. The method of research used in this study is descriptive quantitative, and the source of primary data is interviews and questionnaires, while that of secondary data comprises a company report. The data were processed with SimaPro software and using the Eco Indicator 99 method. The results of the study suggest that the greatest impact on the environment is respiratory inorganic, with a value of 221.69 Pt, being caused by the process of chrome tanning due to the application of the process based on the use of chromium fuel, using a chrome raw material. As an alternative improvement to reduce chrome tanning waste content in chromium, the addition of coagulants CaO and FeCl3 is prioritized. To do so, this study underscores how handling the environmental impacts in the leather industry in a clean production way is to preserve human health and the ecosystem of the places around this industry while attempting to achieve this objective.